Philosophy, Archaeology and the Bible: Is Emperor Julian's Contra Galilaeos a Plausible Critique of Christianity? - Aiken, David Wyatt (Journal for late antique religion and culture, 2017)
In Contra Galilaeos, Julian makes the case that in the writings of Moses Yahweh is not the Most High' God, but simply one of many national gods (the biblical term is angels' or sons of god/s', ??? ?? , ??? ???? , or ??? ?????? ) of the ancient Near Eastern world, who received Israel as an inheritance from the hand of the Most High. Christians claim the Jewish Yahweh as their God, and appeal to the Hebrew writings to identify the qualities of that God; but Julian claims that the Jewish writings clearly depict Yahweh as a subordinate tribal god, who was neither the Creator (demiurge), nor to be identified with the God of Abraham, nor to be equated with the Most High (Hypsistos), apportioning God of Deut. 32:8-9. Julian extrapolates from this stunning premise that there is therefore no compelling comparison to be advanced between Yahweh, as depicted in the Hebrew Scriptures, and the God proclaimed by the Christians. Julian's argument will receive unexpected support from the 1929 archaeological findings of Ugarit, which have had a significant impact on helping to identify ancient Near Eastern gods alluded to in the documents of the Hebrew Bible. Indeed, Julian's analyses of the texts of the Hebrew Bible are sustained by nothing less than the accumulated mythological weight of the entire ancient Near East.